Pemetaan tingkat kerawanan alih fungsi lahan sawah untuk mendukung perencanaan perlindungan lahan pertanian pangan berkelanjutan di kampung Prafi Mulya kabupaten Manokwari - Yosefa Monica Mileni Nainggolan; Samsul Bachri; Budiyono; Baso Daeng; Imam Widodo (Agrotek, 2021)
The purpose of this study was to develop data and information on potential locations to analyze the level of vulnerability to conversion of paddy fields in Prafi Mulia village. This research is a descriptive study with survey methods by using questionnaire and taking coordinates of paddy fields using the Avenza Maps application. The results found that there are three level of vulnerability to conversion of paddy fields, namely very vulnerable, vulnerable, and not vulnerable. After overlapping the maps, it was found that the land that is very vulnerable to land conversion is 59.5 ha from 13 farmer groups. The farmer group with the highest level of vulnerability is Harapan Makmur with an area of ​​14 ha and the lowest level of vulnerability is the Sidodadi Farmer Group with an area of ​​0.5 ha. There are 138 ha of land with the highest vulnerability category and the highest vulnerability is found on land belonging to the Karya Bakti farmer group, which is 16 ha and the lowest is the Rukun Tani, Sido Dadi, and Sumber hasil farmer groups with an area of ​​5 ha. In the non-prone category, there is an area of ​​81 ha with the highest value in the Tekat Maju farmer group of 21 ha and the lowest in the Karya Bakti, Sido Mukti, and Margo Mulyo farmer groups with an area of ​​1 ha.